Retinitis associated with double infection of Epstein–Barr virus and varicella-zoster virus: A case report. Issue 31 (August 2018) - Sato, Tomohito; Kitamura, Riki; Kaburaki, Toshikatsu; Takeuchi, Masaru
Abstract: Rationale: Chronic uveitis with immunosuppressive agents could develop chronic herpetic retinitis with varicella-zoster virus (VZV) or herpes simplex virus (HSV). Ocular Epstein–Barr virus (EBV) infection develops uveitis and vitritis, but the clinical feature of EBV retinitis is not typical as a viral retinitis. EBV retinitis is rare, and only a few cases of EBV retinitis have been reported. Herein, we describe a case of retinitis with EBV and VZV which were the primary viruses verified by multiplex polymerase chain reaction (PCR). Patient concerns: A 75-year-old woman suffered from sudden visual loss in the left eye. She had been diagnosed with rheumatoid arthritis. At presentation, visual acuity (VA) was 20/400 in the left eye. Slit lamp examination disclosed fine white keratic precipitates with infiltrating cells and dense vitreous opacities in the anterior segment and vitreous. Fundus photographs showed multifocal chorioretinal scars in macula and peripheral retina, and granular lesions surrounding arcade vessels. Diagnoses: Ocular toxoplasmosis was primarily suspected. Interventions: However, serological test showed negative of toxoplasmosis. Therefore, a diagnostic and therapeutic vitrectomy was performed. Vitreous fluid sample was used for multiplex PCR for detection of human herpesvirus (HHV) -1 to -8, toxoplasmosis and toxocariasis. Outcomes: Multiplex PCR detected 5.8 × 10 5  copies/mL of EBV-deoxyribonucleic acid (DNA), and 3.6 × 10 6  copies/mL of VZV-DNA in the sample. Therefore, we could diagnose the unidentified panuveitis a retinitis associated with double infection of EBV and VZV. At 85 days after the vitrectomy, VA of the left eye recovered to be 20/16. Lessons: Elderly patients under immunosuppression may be susceptible to develop retinitis associated with infection of multiple HHVs, and multiplex PCR is an excellent tool to diagnose an unidentified panuveitis resembling this case.